The systemization of field register’s data to application for area based payment in case of an estate - Bónai, András (Acta Agraria Kaposváriensis, 2006)
I stayed my informatical practice at an estate. It manages plough- land plant growing on 2000acres (app. 80 fields). After support to the European Union, the most of estate’s areas was entrance to the Single Area Payment Scheme, and to the Agricultural Environmental Farming Program. Some of these fields were not entrance one of financial aid programs. Others were entrance both of them. The topographical number system is not as same as MEPAR system, so the proportions of parcels are different form the previous registry. Other problem is that every field has 4 identify number at least. Single area system is seriously important to require tenders of EU. Persistently manage and register items of agricultural parcels is a very difficult thing. I would like to solve these problems under my 3-month informatical practice. I integrated the necessary data to Excel table. The table conformation was similar to the previously used field register system. Field works and date was registered in table.
Keywords: topographical number; registry number; agricultural parcel; field register